Common TLR1 Genetic Variation Is Not Associated with Death from Melioidosis, a Common Cause of Sepsis in Rural Thailand - Chantratita, Narisara (Public Library of Science, 2014)
Melioidosis, infection caused by the Gram-negative bacterium Burkholderia pseudomallei, is a common cause of sepsis in northeast Thailand. In white North Americans, common functional genetic variation in TLR1 is associated with organ failure and death from sepsis. We hypothesized that TLR1 variants would be associated with outcomes in Thais with melioidosis. We collated the global frequencies of three TLR1 variants that are common in white North American populations: rs5743551 (-7202A/G), rs4833095 (742A/G), and rs5743618 (1804G/T). We noted a reversal of the minor allele from white North American subjects to Asian populations that was particularly pronounced for rs5743618. In the Utah residents of European ancestry, the frequency of the rs5743618 T allele was 17% whereas in Vietnamese subjects the frequency was >99%. We conducted a genetic association study in 427 patients with melioidosis to determine the association of TLR1 variation with organ failure or death. We genotyped rs5743551 and rs4833095. The variants were in high linkage disequilibrium but neither variant was associated with organ failure or in-hospital death. In 300 healthy Thai individuals we further tested the association of TLR1 variation with ex vivo blood responses to Pam3CSK4, a TLR1 agonist. Neither variant was robustly associated with blood cytokine responses induced by Pam3CSK4. We identified additional common variation in TLR1 by searching public databases and the published literature and screened three additional TLR1 variants for associations with Pam3CSK4-induced responses but found none. We conclude that the genetic architecture of TLR1 variation differs substantially in southeast Asians compared to other populations and common variation in TLR1 in Thais is not associated with outcome from melioidosis or with altered blood responses to Pam3CSK4. Our findings highlight the need for additional studies of TLR1 and other innate immune genetic modulators of the inflammatory host response and determinants of sepsis in southeast Asian populations.